Penser le Cthulhucène et son géotraumatisme : le cas Cyclonopedia de Reza Negarestani - Fabien Richert (ReS Futurae)
In Iranian philosopher Reza Negarestani’s Cyclonopedia: Complicity with Anonymous Materials (2008), concepts by Gilles Deleuze and Félix Guattari intersect with the cosmic deities imagined by H.P. Lovecraft, occult Zoroastrian relics explain John Carpenter’s horrific science fiction imagination, and develop a most extravagant hypothesis: oil, a “tellurian entity” imprisoned in the deep layers and formations of the earth, has been waiting for a long time to be released from the depths of the earth and to spread into the atmosphere. Negarestani’s work presents oil as the real subject of history, humanity as its host, the industrial revolution as its point of no return. The esoteric allure and sophistication of the argument, set against a backdrop of conspiracy theories, draws the reader into a paranoid delusion marked by a conspiracy fomented on a quasi-cosmic scale: the burning of oil, seen as a fundamental step in its own “satanic agenda”, is the key moment from which it can spread into the atmosphere. Capitalism extended to a global scale is then seen as the most adequate solution to the uninterrupted burning of fossil fuels. In this article, we would like to reflect on the contributions of Negarestani’s work to the field of climate fictions. We will begin by presenting his geophilosophical dimension before returning in more detail to his imaginary world under the influence of an evil entity. We will then show how Cyclonopedia presents itself as a speculative climate fiction that adopts a neo-materialist perspective inspired by the approach of speculative realism.